Selective filters of translational molecular diffusion dynamics in white matter microstructures with preclinical and clinical MRI - Saidman, Ezequiel L. (2023)
Magnetic resonance imaging is one of the most widely used methods for non-invasive medical imaging. Gradient modulation sequences can selectively extract quantitative information at micrometer and sub-micrometer scales that might be relevant for clinical applications. We approach this topic using white matter phantoms by observing the contrast generated by Non-uniform Oscillating Gradient Spin Echo (NOGSE) sequences to selectively filter the signal of molecules confined in compartments of specific sizes. The NOGSE contrast is determined by subtracting different OGSE acquisitions on a clinical scanner. Our results demonstrate a microscopic tortuosity mechanism that provides microstructural information on short time scales.